The Effects of Forest Harvesting on Total and Methylmercury Concentrations in Surface Waters Depend on Harvest Practices and Physical Site Characteristics - Eklöf, Karin; de Wit, Heleen; Eckley, Chris S.; Eagles-Smith, Collin A.; Eggert, Susan L.; Mackereth, Robert W.; Skyllberg, Ulf; Ukonmaanaho, Liisa; Verta, Matti; Allan, Craig; Emilson, Erik J. S.; Kidd, Karen A.; et al. (American Chemical Society, 2025)
Forest harvesting can lead to mercury (Hg) mobilization from soils to aquatic habitats and promote the transformation of inorganic Hg to highly neurotoxic and bioaccumulative methyl-Hg (MeHg). Multiple past studies reveal broad variation of stream water MeHg and total Hg (THg) concentration responses to forest harvesting, which has confounded messaging to forest and resource managers. To advance beyond divergent and sometimes contradictory findings, we synthesized information for 23 previously studied catchments in North America and Fennoscandia and compiled a uniform set of soil, landscape, and harvesting properties to identify forest management, riparian, and hillslope factors that influence responses of stream water MeHg and THg concentrations. From this synthesis, we found catchments with high soil moisture and organic soil layers >100 cm to be at highest risk for disturbance-induced increases in MeHg formation after harvest but not necessarily affecting concentrations of MeHg in stream waters. Instead, the combination of MeHg formation in soils along with factors that affect mobilization with runoff to streams most influenced how forest harvest affects MeHg concentrations in stream waters.
Keywords: forestry; clear-cut; methylmercury; soil disturbance; mitigation methods